Rheological properties of mango puree and process development of mango sheet - S. Phaokuntha (2018)
The rheological properties of mango puree were studied and measured using a controlled-stress/strain rheometer. Mango puree was prepared from naturally ripened mangoes. The rheological properties were pseudoplastic or shear thinning behavior. Mathematical models of Bingham, Power Law and Herschel-Bulkley model were used to predict the flow behavior. Root Mean Squared Error (RMSE), adjusted coefficient of determination (R2 adj) and reduced chi-square (?2) were calculated in order to verify the models. The Power Law model was found to be the best model for describing the rheological properties of mango puree. A Central Composite Design (CCD) consisting of two-factors factorial with quadratic model was used for the process development of mango sheet. The factors were citric acid and refined sugar added. Subsequently, preheated mango puree was dried using temperature of 60°C with 0.5 m/s air velocity by tray dryer. A Response Surface Methodology (RSM) was used to optimize the amount of citric acid and sugar addition. Consequently, mango sheet was evaluated for sensory characteristics. It was found that consumers (n=50) most accepted mango sheet using 1.5 g of citric acid and 10 g of refined sugar. There was no relationship found between citric acid and sugar contents on colour, flavor, and texture acceptance (P > 0.05). However, the relationship between citric acid and sugar contents on sourness, sweetness and overall acceptability were found (P=0.05) with R2 adj of 92.50, 34.13 and 71.61%, respectively.